Preparation method of nano-confined catalytic membrane and method for removing organic pollutants by synergistic ozone micro-nano bubbles

CN122875245APending Publication Date: 2026-10-09XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611188482.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]一是臭氧的物理传质效率低

Benefits of technology

[0024] 1. Excellent chemical and structural stability: Through the "nano confinement effect" of the MOF-derived carbon skeleton, the Fe/Mn metal active components are firmly anchored in the nanochannels, effectively inhibiting the aggregation, migration and loss of metal nanoparticles (maintaining stable activity during 720 min of continuous operation), and significantly reducing the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875245A_ABST
    Figure CN122875245A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a nano-confined catalytic membrane and a method for removing organic pollutants by synergistic ozone micro-nano bubbles, and belongs to the field of environmental remediation and advanced oxidation technology. The application constructs a triple synergistic system of "membrane filtration-nano-confined catalysis-micro-nano bubbles", utilizes the hierarchical pore structure of Mn-MOF-74, adopts a "host-guest" confinement strategy to in-situ encapsulate iron nanoparticles, pyrolyzes at 500 DEG C to obtain a Fe / Mn bimetallic porous carbon catalyst, and loads the catalyst on the surface of a support membrane. In the treatment process, the forced convection effect of the membrane filtration mode is used to weaken the interface diffusion layer, the high mass transfer efficiency of O3-MNBs and the nano-confined environment of active sites are combined, active species such as hydroxyl radicals, singlet oxygen and superoxide radicals are induced to be generated, and efficient removal of pollutants such as oxalic acid, antibiotics and dyes is realized. The system has the advantages of strong stability, wide pH adaptability and the like, and provides an efficient solution for the advanced treatment of refractory organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental remediation materials and water treatment technology, specifically relating to a method for preparing a nano-confined catalytic membrane and a method for synergistically removing organic pollutants using ozone micro-nano bubbles. Background Technology

[0002] With rapid industrialization and urbanization, the frequent occurrence of emerging organic pollutants (ECs) in water bodies, such as pharmaceutical wastewater, endocrine disruptors, and pesticide residues, has posed a serious threat to global ecological security and human health. Traditional biological treatment and conventional water treatment processes often fail to achieve complete mineralization of these chemically stable persistent organic pollutants. Therefore, advanced oxidation technologies (AOPs) based on the generation of strong oxidizing free radicals have become a research hotspot.

[0003] Among numerous advanced oxidation technologies, catalytic ozone oxidation shows great promise in the field of advanced water treatment due to its ability to efficiently generate non-selective hydroxyl radicals (·OH) and its rapid reaction rate. However, the practical application of heterogeneous catalytic ozone oxidation has long been constrained by two key bottlenecks:

[0004] First, ozone has low physical mass transfer efficiency. Traditional gas distribution methods mainly produce macroscopic bubbles with small gas-liquid interface areas, rapid rise in water, and short residence times. This results in ozone dissolution rates being far lower than its catalytic activation rates, limiting the overall efficiency of the oxidation reaction.

[0005] Secondly, the stability of the catalyst and the utilization rate of active sites are insufficient. Active metal nanoparticles on the surface of traditional supported catalysts are prone to aggregation during the reaction process, leading to a reduction in specific surface area and deactivation of active sites. More seriously, the leaching of metal ions in an oxidizing environment not only shortens the catalyst's lifespan but may also cause secondary pollution. Although nano-confinement can effectively inhibit the migration and leaching of metal particles, how to synergistically couple it with physical mass transfer enhancement technologies (such as micro / nanobubbles) and efficient reactor forms (such as membrane reactors) across dimensions to construct a highly efficient micro-interface system that can simultaneously solve the problems of "mass transfer" and "activation" remains a direction that urgently needs breakthrough in current water treatment technology research and development. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a nano-confined catalytic membrane and a method for synergistically removing organic pollutants using ozone micro-nano bubbles. The aim is to optimize the mass transfer efficiency of the ozone micro-interface and the chemical stability of the catalytic sites by coupling "nano confinement" and "micro-nano bubble membrane filtration", so as to achieve efficient and stable degradation of emerging organic pollutants (such as oxalic acid, antibiotics and dyes) in water.

[0007] On one hand, the present invention provides a method for preparing a nano-confined catalytic membrane, comprising the following steps:

[0008] S1. Dissolve the manganese source and surfactant in a mixed solvent to form solution A; dissolve the ligand in the mixed solvent to form solution B; slowly add solution B to solution A, stir and react at 25°C for 18 h, then centrifuge, wash and dry to obtain the Mn-MOF-74 precursor with a rod-like structure;

[0009] S2. Using a subject-object confinement strategy, the Mn-MOF-74 precursor is dispersed in an iron source solution for impregnation treatment, so that iron ions diffuse into the nanopores of Mn-MOF-74, and iron-loaded MOF composite is obtained after post-treatment.

[0010] S3. The iron-supported MOF composite is pyrolyzed under an inert atmosphere to obtain a nano-confined catalyst.

[0011] S4. After the catalyst and binder are mixed and dispersed, they are loaded onto the surface of the support membrane using a vacuum-assisted self-assembly method, and then dried to obtain the nano-confined catalytic membrane.

[0012] Preferably, in step S1, the manganese source is manganese acetate tetrahydrate, the ligand is trimesic acid, and the surfactant is polyvinylpyrrolidone; the mass ratio of the manganese source to the surfactant is 1:1, and the molar ratio of the manganese source to the trimesic acid is 3:2; the mixed solvent is a mixture of ethanol and water with a volume ratio of 1:1.

[0013] Preferably, in step S2, the iron source is ferric nitrate nonahydrate; the mass-to-volume ratio of the Mn-MOF-74 precursor to the ferric nitrate nonahydrate ethanol / water mixed solution is 1 g : 125 mL, the concentration of the iron source in the ferric nitrate nonahydrate ethanol / water mixed solution is 2 mM, and the immersion time is 30 min.

[0014] Preferably, in step S3, the pyrolysis temperature is 400-600℃, the inert atmosphere is nitrogen, and the heating rate is 5℃·min. -1 The heat preservation time is 2 hours.

[0015] Preferably, in step S3, the pyrolysis temperature is 500 °C.

[0016] Preferably, in step S4, the binder is polyvinylidene fluoride and the dispersion is anhydrous ethanol; the mass ratio of the catalyst to the binder is 1:0.12; the drying temperature is 60 °C and the drying time is 12 h.

[0017] Preferably, in step S4, the supporting membrane is an organic filter membrane; the thickness of the active catalytic layer of the obtained catalytic membrane is 91.5 μm.

[0018] On the one hand, the present invention also provides a nano-confined catalytic membrane prepared by the above preparation method.

[0019] Furthermore, the present invention also provides a method for removing organic pollutants using the above-mentioned nano-confined catalytic membrane, comprising the following steps:

[0020] Ozone micro-nano bubbles (O3-MNBs) are generated by an ozone micro-nano bubble generator and introduced into a reaction system containing the target pollutant to enhance mass transfer.

[0021] A pump is used to drive a reaction system containing O3-MNBs through the nano-confined catalytic membrane. In the micro-region at the catalytic membrane interface, the pollutants, ozone micro-nano bubbles and confined active sites are fully contacted by forced convection mode to carry out catalytic oxidation reaction.

[0022] Preferably, the organic pollutant is at least one of oxalic acid, tetracycline, oxytetracycline, chlortetracycline, rhodamine B, methylene blue, and methyl orange.

[0023] The present invention has the following beneficial technical effects:

[0024] 1. Excellent chemical and structural stability: Through the "nano confinement effect" of the MOF-derived carbon skeleton, the Fe / Mn metal active components are firmly anchored in the nanochannels, effectively inhibiting the aggregation, migration and loss of metal nanoparticles (maintaining stable activity during 720 min of continuous operation), and significantly reducing the risk of secondary pollution.

[0025] 2. Significantly enhanced physical mass transfer efficiency: By coupling ozone micro-nano bubble (O3-MNBs) technology with membrane filtration forced convection mode, the huge gas-liquid specific surface area, high internal pressure and slow rise speed of micro-nano bubbles are utilized to fundamentally break through the bottleneck of low mass transfer efficiency of traditional ozone oxidation and improve the effective dissolved concentration of ozone at the catalytic interface.

[0026] 3. Excellent catalytic oxidation activity: Utilizing the synergistic effect of the Fe / Mn redox couple (Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II)), it efficiently induces the generation of hydroxyl radicals (·OH) and singlet oxygen (·OH) through a multi-pathway reaction mechanism. 1 O2) and superoxide radicals (O2) ·- It achieves near-complete degradation of various recalcitrant organic compounds within 60 minutes.

[0027] 4. Broad applicability and environmental compatibility: The system provided by this invention can maintain excellent anti-interference ability and mineralization efficiency in a wide pH range (3.0-9.0) and under conditions of multiple coexisting ions and complex actual water matrix, and has great potential for engineering applications. Attached Figure Description

[0028] Figure 1 SEM images of nano-confined Fe2Mn-500 prepared in Example 1 of this invention at different magnifications;

[0029] Figure 2 This is an EDS mapping image of Fe2Mn-500 prepared in Example 1 of the present invention at 1 μm.

[0030] Figure 3 HRTEM image of Fe2Mn-500 prepared in Example 1 of this invention;

[0031] Figure 4 This is an EDS mapping image of Fe2Mn-500 prepared in Example 1 of the present invention at 200 nm.

[0032] Figure 5 SEM images of the cross-section of the Fe2Mn-500 catalytic membrane prepared in Example 1 of this invention at different magnifications;

[0033] Figure 6 This is an EDS mapping image of the cross-section of the Fe2Mn-500 catalytic membrane prepared in Example 1 of this invention, obtained from a SEM image.

[0034] Figure 7 These are top-view SEM images of the Fe2Mn-500 catalytic film prepared in Example 1 of this invention at different magnifications;

[0035] Figure 8 The XRD patterns of Mn-MOF, Fe2Mn, and pyrolysis products at different temperatures prepared in Examples 1, 2, and 3 of this invention are shown below.

[0036] Figure 9 High-resolution XPS spectra of Fe 2p(a) and Mn 2p(b) of Mn-MOF, Fe2Mn, and pyrolysis products at different temperatures prepared in Examples 1, 2, and 3 of this invention.

[0037] Figure 10The following are comparative graphs showing the performance evaluation of oxalic acid degradation by different oxidation systems and catalysts provided in Comparative Examples 1-4 and Examples 1-4 of this invention: (a) is a comparative graph showing the performance evaluation of oxalic acid degradation by different oxidation systems (O3, O3-MNBs, O3+Fe2Mn-500 and O3-MNBs+Fe2Mn-500) in Comparative Examples 1 and 2; (b) is a comparative graph showing the performance evaluation of oxalic acid degradation by different oxidation systems (O3 membrane filtration, O3-MNBs membrane filtration, O3+Fe2Mn-500 membrane filtration and O3-MNBs+Fe2Mn-500 membrane filtration) in Comparative Examples 1 and 2; (c) is a comparative graph showing the performance evaluation of oxalic acid degradation by catalysts prepared by pyrolysis at different temperatures in Examples 1, 2 and 3; and (d) is a comparative graph showing the performance evaluation of oxalic acid degradation by confined bimetallic catalysts and monometallic catalysts prepared in Comparative Examples 3, 4 and 4.

[0038] Figure 11 The figures show the catalytic degradation performance test results provided in Examples 5-11 of this invention; where (a) shows the degradation curves of oxalic acid (OA), antibiotics (TC, OTC, CTC), and synthetic dyes (RhB, MB, MO) for various pollutants in Examples 5, 6, 7, and 9; (b) shows the effect of different pH conditions on degradation performance in Example 8; (c) shows the effect of different coexisting inorganic anions on degradation performance in Example 10; and (d) shows the comparison of degradation efficiency in actual water matrices such as tap water, groundwater, surface water, and secondary effluent in Example 11.

[0039] Figure 12 This is a schematic diagram of the experimental setup for the ozone micro-nano bubble synergistic catalytic membrane reaction system used in Example 12 and Test Example 4 of the present invention.

[0040] Figure 13 The graph shows the long-term filtration stability test results of the ozone micro-nano bubble synergistic catalytic membrane reaction system used in Example 12 and Test Example 4 of this invention after continuous operation for 720 min.

[0041] Figure 14 Free radical quenching experiments were conducted in Test Example 3 of this invention by adding different concentrations of tert-butanol (TBA) (a), furfuryl alcohol (FFA) (b), and p-benzoquinone (p-BQ) (c). Detailed Implementation

[0042] The present invention will be further described in detail below with reference to specific embodiments, comparative examples and accompanying drawings.

[0043] Example 1: Preparation of Fe2Mn-500 nano-confined catalytic membrane and its application in oxalic acid wastewater treatment

[0044] This embodiment demonstrates the performance of the preparation process and triple synergistic system provided by the present invention in the removal of oxalic acid, a typical recalcitrant organic compound.

[0045] 1. Preparation of nano-confined bimetallic catalytic powder:

[0046] Synthesis of S1, Mn-MOF-74 precursor: 1.47 g of manganese acetate tetrahydrate and 1.47 g of polyvinylpyrrolidone (PVP) were completely dissolved in 100 mL of a mixed solvent of ethanol and water (volume ratio 1:1) to form solution A; 0.84 g of trimesic acid (H3BTC) was dissolved in another 100 mL of the same mixed solvent to form solution B. Solution B was slowly added to solution A under strong magnetic stirring, and the reaction was continuously stirred at 25 °C for 18 h. After the reaction was complete, the precipitate was collected by centrifugation, washed three times successively with deionized water and anhydrous ethanol, and dried under vacuum at 60 °C to obtain Mn-MOF-74 with a rod-like structure.

[0047] S2. Host-guest confined loading of active components: Weigh 0.2 g of the above Mn-MOF-74 powder and disperse it in 25 mL of 2 mM ferric nitrate nonahydrate ethanol / water solution. After ultrasonic dispersion, stir magnetically for 30 min at room temperature to allow Fe... 3+ Ions diffuse into the nanopores of the MOF. The solid was then collected by filtration and dried at 60 °C.

[0048] S3. In-situ pyrolysis and topological transformation: The dried iron-supported composite was placed in a tube furnace and pyrolyzed at 5 °C·min under a N2 atmosphere. -1 The temperature was increased to 500 °C at a heating rate and held for 2 h. The pyrolysis process transformed the MOF framework in situ into a defect-rich porous carbon matrix, while simultaneously reducing and confining the Fe / Mn components within it to carbon nanopores, thus preparing Fe2Mn-500 catalyst powder.

[0049] 2. Construction of nano-confined catalytic membranes:

[0050] S4. 0.03 g of Fe2Mn-500 catalyst powder was dispersed in 5 mL of anhydrous ethanol, and 20 μL of polyvinylidene fluoride (PVDF, 10% by mass) was added as a binder. After ultrasonic treatment with a probe for 30 min to form a uniform catalyst suspension, it was uniformly loaded onto the surface of the support membrane using a vacuum-assisted self-assembly (VASA) method and vacuum dried at 60 °C for 12 h. Finally, a nano-confined catalytic membrane with an active catalyst layer thickness of 91.5 μm was obtained.

[0051] 3. Pollutant removal test:

[0052] The synergistic reaction system constructed using this invention was used to introduce wastewater containing 100 mg / L oxalic acid. The ozone micro-nano bubble generator was activated, and the generated O3-MNBs were introduced into the water body. A pump then drove the wastewater through the catalytic membrane in a filtration mode. After 60 minutes of reaction, the wastewater was... Figure 10 As can be seen from d, the removal rate of oxalic acid reached 99.83%.

[0053] Example 2: Catalytic membrane prepared by pyrolysis at a lower temperature (400 °C) and its performance.

[0054] This embodiment is used to compare the effect of decreasing pyrolysis temperature on confined structure and activity.

[0055] 1. Preparation steps: basically the same as in Example 1, except that the pyrolysis temperature in step S3 is set to 400℃.

[0056] 2. Performance Testing: Oxalic acid at a concentration of 100 mg / L was degraded under the same test conditions as in Example 1. After a reaction of 40 min, the degradation was carried out by... Figure 10 c indicates that the removal rate of oxalic acid is 72.80%.

[0057] Example 3: Catalytic membrane prepared by high-temperature (600 °C) pyrolysis and its performance

[0058] This embodiment is used to compare the effects of increasing pyrolysis temperature on confined structure and activity.

[0059] 1. Preparation steps: basically the same as in Example 1, except that the pyrolysis temperature in step 3 is set to 600℃.

[0060] 2. Performance Testing: Under the same test conditions, after a reaction of 60 minutes, by... Figure 10 c indicates that the oxalic acid removal rate was 80.45%. Experiments show that excessively high pyrolysis temperatures lead to minor damage to the nano-confined structure, resulting in a decrease in catalytic activity compared to Example 1.

[0061] Example 4: Preparation and Performance of Single Metal Catalysts

[0062] This comparative example provides a method for preparing a single-metal catalyst and its performance determination.

[0063] 1. Preparation steps: Basically the same as in Example 1, except that no iron source (or manganese source) was added during the preparation process, only a manganese source (or iron source) was introduced. The obtained single metal catalysts were named Mn-500 and Fe-500, respectively.

[0064] 2. Performance Testing: Performance test results: Under the same test conditions, catalytic degradation tests were conducted on oxalic acid. The results are as follows: Figure 10As shown in d: when using the single metal catalyst Fe-500, the removal rate of oxalic acid after 60 min of reaction was only 68.49%; when using the single metal catalyst Mn-500, the removal rate of oxalic acid after 60 min of reaction was 97.73%, but the removal rate was only 73.61% after 40 min; while Example 1 (Fe2Mn-500 bimetallic catalyst) could completely degrade oxalic acid within 40 min.

[0065] Example 5: Degradation performance of the synergistic system for tetracycline (TC) antibiotics

[0066] This embodiment is used to demonstrate the superior performance of the synergistic system provided by the present invention in removing typical antibiotic contaminants.

[0067] 1. Experimental Procedure: The Fe2Mn-500 nano-confined catalytic membrane prepared in Example 1 was used. The wastewater to be treated was simulated antibiotic wastewater containing 20 mg / L tetracycline. The ozone micro-nano bubble generator was turned on, and the ozone dosage was controlled to be consistent with that in Example 1.

[0068] 2. Experimental Procedure: A pump was used to drive wastewater containing air bubbles through a catalytic membrane in filtration mode. Because the Fe / Mn bimetallic active sites are confined within carbon nanopores, and O3-MNBs provide an extremely high gas-liquid mass transfer interface, the wastewater comes into full contact with a high density of reactive oxygen species during the transmembrane process.

[0069] 3. Experimental Results: From Figure 11 As shown in Figure a, the degradation rate of tetracycline reached over 99% after only 10 minutes of reaction. The results indicate that the system of this invention can achieve rapid degradation and deep mineralization of antibiotic molecules, effectively solving the problem of antibiotics being difficult to remove in conventional water treatment.

[0070] Example 6: Broad-spectrum degradation performance of the synergistic system against multiple antibiotics

[0071] This embodiment further verifies the universality of the system for similar antibiotics.

[0072] 1. Experimental Procedure: Oxytetracycline (OTC) and chlortetracycline (CTC) solutions with an initial concentration of 20 mg / L were prepared. Degradation experiments were conducted using the Fe2Mn-500 catalytic membrane prepared in Example 1, with all operating parameters remaining constant.

[0073] 2. Experimental Results: The experimental results showed that the removal rates of oxytetracycline and chlortetracycline remained stable at over 98.5% within a 60-minute reaction time. This was achieved by comparing the degradation kinetic curves of different antibiotics (e.g., ...). Figure 11As shown in a), the system exhibits strong versatility for tetracycline antibiotics. This is attributed to the fact that the multivalent metal cycle (Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II)) in the nano-confined environment can continuously and stably activate ozone to generate a large number of free radicals, unaffected by minor differences in specific molecular structures.

[0074] Example 7: Decolorization and degradation performance of the synergistic system for synthetic dyes (Rhodamine B)

[0075] This embodiment is used to demonstrate the ability of the system of the present invention to treat high-chromatic organic pollutants (such as synthetic dyes).

[0076] 1. Experimental Procedure: The Fe2Mn-500 catalytic membrane prepared in Example 1 was used. The experiment was conducted on the treatment of Rhodamine B (RhB) dye wastewater with an initial concentration of 50 mg / L.

[0077] 2. Experimental Results: From Figure 11 As shown in Figure a, the decolorization rate of Rhodamine B approached 100% within 30 minutes of reaction; after 60 minutes, the solution became completely colorless and transparent. Characterization of the membrane after the reaction revealed no residual physical adsorption of dye molecules on the membrane surface, proving that the pollutants were completely decomposed through catalytic oxidation. This example demonstrates the application prospects of this system in the field of advanced treatment of dyeing and printing wastewater.

[0078] Example 8: Adaptability test over a wide pH range (3-9)

[0079] This embodiment aims to verify the stability and effectiveness of the system of the present invention in wastewater with different pH levels.

[0080] 1. Experimental Procedure: Oxalic acid at a concentration of 100 mg / L was used as the target pollutant. The initial pH of the wastewater was adjusted to 3, 5, 6, 7, and 9, respectively, using 0.1 mol / L HCl and NaOH solutions. The Fe2Mn-500 catalytic membrane prepared in Example 1 was operated in synergistic mode.

[0081] 2. Experimental Results: From Figure 11 As shown in b, the oxalic acid removal rate remained above 99% under acidic conditions (pH=3), neutral conditions (pH=7), and alkaline conditions (pH=9).

[0082] 3. Analytical Conclusions: Traditional ozone catalysts are often effective only within a specific pH range, while the nano-confined catalytic membrane of this invention maintains extremely high activity across a pH range of 3.0–9.0. This is mainly because the microenvironment within the nano-confined space is relatively independent, the carbon shell protects the metal active centers from direct passivation by strong acids or bases, and it effectively induces multi-pathway activation of ozone under different pH conditions. This embodiment provides strong data support for the application of this technology in treating acidic mining wastewater or alkaline dyeing wastewater.

[0083] Example 9: Broad-spectrum degradation performance of the synergistic system for various synthetic dyes (MB, MO)

[0084] This embodiment aims to further verify the universal processing capability of the system of the present invention for synthetic dyes with different structures.

[0085] 1. Experimental Procedure: The Fe2Mn-500 nano-confined catalytic membrane prepared in Example 1 was used. Simulated dye wastewater containing methylene blue (MB) and methyl orange (MO) at initial concentrations of 20 mg / L was prepared. Operating parameters were set as follows: ozone gas flow rate 50 mL / min.

[0086] 2. Experimental Results: After 60 minutes of reaction, the decolorization rate of the dyes all reached over 99%. According to... Figure 11 Kinetic analysis of a showed that the system exhibited high degradation activity for dyes with different charge properties (anionic and cationic), proving that the catalytic membrane surface has good hydrophilicity and chemical applicability.

[0087] Example 10: Effect of coexisting inorganic anions on degradation performance and anti-interference ability test

[0088] This embodiment is used to evaluate the performance stability of the system of the present invention in a complex environment containing common inorganic ions.

[0089] 1. Experimental Procedure: Using 100 mg / L oxalic acid as the target pollutant, 10 mM of different inorganic anions, including chloride ions (Cl...), were added to the reaction system. - ), nitrate (NO3) - Bicarbonate (HCO3) - ) and hydrogen phosphate (HPO4) 2- ).

[0090] 2. Experimental Results and Analysis: From Figure 11 c indicates that adding Cl - NO3 - and HPO4 2- Afterwards, the degradation rate of oxalic acid only fluctuated slightly, and the degradation rate remained above 98%.

[0091] 3. Conclusion: Traditional advanced oxidation systems are highly susceptible to quenching by background ions, while the nanoconfined structure of this invention provides a certain degree of spatial shielding for active sites, reducing the competition for effective sites by a large number of anions. This embodiment demonstrates that the catalytic membrane has excellent anti-interference capabilities.

[0092] Example 11: Performance Testing in Complex Real-World Aquatic Matrix

[0093] This embodiment aims to demonstrate the reliability of the invention when treating real-world water bodies.

[0094] 1. Experimental Procedure: Four types of real water samples were collected as background substrates: tap water, groundwater, river water, and secondary effluent from a wastewater treatment plant. 100 mg / L of oxalic acid was added to each of the above water samples, and the catalytic membrane described in Example 1 was used for treatment.

[0095] 2. Experimental results are from Figure 11 As can be seen from d, in tap water and groundwater, the removal rate of oxalic acid is almost the same as that of deionized water matrix, reaching over 99%; in surface water and secondary effluent with more complex composition, the degradation rate is slightly slower due to the influence of dissolved organic matter and high salinity, but the removal rate can still reach over 99% within 60 minutes.

[0096] 3. Conclusion: Experimental data fully demonstrate that the nano-confined catalytic membrane of the present invention can overcome the poisoning effect of impurities in complex aqueous matrices on active sites, and has extremely high engineering application value for the deep purification of actual wastewater.

[0097] Example 12: Long-term operational stability test of the catalytic membrane (720 min continuous filtration)

[0098] This embodiment aims to verify the structural mechanical strength and catalytic stability of the catalytic membrane under continuous industrial operation scenarios.

[0099] 1. Experimental Procedure: A continuous flow filtration reaction device was constructed using the Fe2Mn-500 catalytic membrane prepared in Example 1. Oxalic acid at a concentration of 100 mg / L was used as the treatment target. The ozone micro / nano bubble system was turned on and maintained in continuous operation for 720 min. Figure 12 Regularly sample and test the concentration of the effluent.

[0100] 2. Experimental results are from Figure 13 It can be seen that during the 720-minute operation, the removal rate of oxalic acid remained stable at over 94%, with no obvious activity decay observed.

[0101] Comparative Example

[0102] Comparative Example 1: Pure ozone macroscopic aeration system (no catalyst, no micro / nano bubbles)

[0103] This comparative example illustrates the treatment effect of traditional ozone oxidation processes in the absence of catalytic activation and efficient mass transfer methods.

[0104] 1. Experimental Procedure: A conventional ozone generator was used to introduce ozone gas into wastewater containing 100 mg / L oxalic acid through a sand core diffuser (which generates millimeter-sized macroscopic bubbles). No catalytic membrane was placed in the system, and the micro / nano bubble generator was not activated.

[0105] 2. Experimental results: such as Figure 10 a can be known ( Figure 10 After reacting for 60 minutes, the removal rate of oxalic acid was only 11.77% (O3 in a).

[0106] 3. Results Analysis: The results show that due to the extremely short residence time of macroscopic ozone bubbles in water and the limited gas-liquid interface area, the dissolution mass transfer rate of ozone is extremely low. Furthermore, in the absence of a catalyst, ozone can only react with pollutants through direct oxidation, and its oxidizing ability for recalcitrant organic compounds such as oxalic acid is very limited.

[0107] Comparative Example 2: Pure ozone micro-nano bubble system (with efficient mass transfer, no catalyst)

[0108] This comparative example is used to verify the processing limit of the system when relying solely on improved physical mass transfer (micro-nano bubbles) without chemical catalytic activation.

[0109] 1. Experimental Procedure: Using the same ozone dosage and micro / nano bubble generator as in Example 1, O3-MNBs were generated and introduced into wastewater containing 100 mg / L oxalic acid. The nano-confined catalytic membrane prepared in Example 1 was not placed in the system.

[0110] 2. Experimental results: such as Figure 10 a( Figure 10 According to the O3-MNBs in a), the removal rate of oxalic acid was 28.57% after 60 min of reaction.

[0111] 3. Results Analysis: As shown in Comparative Example 1, micro- and nano-bubbles significantly improved the dissolution efficiency and utilization rate of ozone, resulting in a doubling of the removal rate. However, due to the lack of active sites in the system capable of inducing the generation of highly reactive free radicals from ozone, simply relying on improved physical mass transfer is insufficient to achieve efficient mineralization of pollutants. This demonstrates that chemical catalytic activation is key to achieving deep oxidation.

[0112] Comparative Example 3: Single Metal Mn-500 Catalytic Membrane System

[0113] This comparative example is used to verify the superiority of the bimetallic (Fe / Mn) synergistic effect over the monometallic system.

[0114] 1. Preparation steps: The method of Example 1 was followed, except that after obtaining Mn-MOF-74 in step S1, the iron source impregnation process in step S2 was skipped, and pure Mn-MOF-74 was directly pyrolyzed at 500℃ for 2 h to obtain single-metal Mn-500 catalyst powder. Subsequently, the catalyst membrane was constructed in the same way.

[0115] 2. Experimental procedure: Mn-500 catalytic membrane was used in conjunction with ozone micro-nano bubbles to degrade 100 mg / L oxalic acid wastewater.

[0116] 3. Experimental results: such as Figure 10 As can be seen from d, after 60 min of reaction, the removal rate of oxalic acid was 62%, which was much lower than that in Example 1.

[0117] 4. Results Analysis: The results show that although the single-metal manganese sites possess a certain ozone activation capacity, the flux of reactive oxygen species generated by the system is limited due to the lack of interfacial electron transfer cycles between Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II) formed by the iron component. Comparison with Example 1 demonstrates that the bimetallic confined structure described in this invention has a significant synergistic enhancing effect in accelerating ozone decomposition and free radical generation.

[0118] Comparative Example 4: Single Metal Fe-500 Catalytic Membrane System

[0119] This comparative example is used to compare with Example 1 to further verify the synergistic effect of electron transfer generated by the bimetallic (Fe / Mn) combination in the nano-confined space.

[0120] 1. Preparation steps: Basically the same as in Example 1, except that Mn-MOF-74 is not used as a precursor, but conventional porous carbon material is used as a support. Ferric nitrate of the same mass fraction is loaded by impregnation, followed by pyrolysis at 500°C for 2 h to obtain single-metal Fe-500 catalyst powder. A catalytic membrane is then constructed according to the method in Example 1.

[0121] 2. Experimental procedure: Fe-500 catalytic membrane was used in conjunction with ozone micro-nano bubbles (O3-MNBs) to degrade oxalic acid wastewater with an initial concentration of 100 mg / L.

[0122] 3. Experimental results: such as Figure 10 As shown in d, after 60 min of reaction, the removal rate of oxalic acid was 58%.

[0123] 4. Results Analysis: Comparison of Comparative Example 3 and Example 1 shows that the catalytic efficiency of single metals Fe or Mn is significantly lower than that of the bimetallic system. This confirms that the coupling of the Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II) redox couples within the nanopores in this invention can significantly accelerate electron circulation, thereby more efficiently activating ozone to generate free radicals.

[0124] Comparative Example 5: Fe2Mn-500 non-filtering operation mode

[0125] This comparative example is used to verify the significant advantages of the "membrane filtration mode (forced convection)" over the traditional "stirred reaction mode (diffusion mass transfer)" and to highlight the role of the "membrane" in the triple synergy.

[0126] 1. Experimental Procedure: The Fe2Mn-500 catalyst powder prepared in Example 1 was used to support and form a film. The procedure was basically the same as in Example 1, except that a pump was not used to drive wastewater through the catalyst membrane in a filtration mode.

[0127] 2. Experimental procedure: In this mode, pollutant molecules and bubbles mainly reach the catalyst surface through the random diffusion motion of the fluid.

[0128] 3. Experimental results: such as Figure 11 As can be seen, after 60 min of reaction, the removal rate of oxalic acid was 88.62%, and the reaction kinetic constant was much lower than that of the filtration mode in Example 1.

[0129] 4. Results Analysis: The results show that even when using the same confined catalyst and micro / nano bubbles, the degradation efficiency decreases significantly without membrane filtration operation. This is because the "forced convection" effect in membrane filtration effectively weakens the diffusion layer thickness at the catalyst interface, forcing ozone bubbles and pollutants to "collide" with the confined active sites as they pass through the membrane channels. This comparative example strongly supports the inventiveness of the triple synergistic membrane filtration system claimed in the claims.

[0130] Test case

[0131] Test Example 1: Microstructure and Component Distribution Test of Catalyst

[0132] This test example aims to verify whether the Fe2Mn-500 catalyst prepared in this invention has successfully achieved nano-confinement of bimetallic sites and whether it inherits the high specific surface area integral level structure of the precursor.

[0133] 1. Testing Methods: The morphology and elemental distribution of the catalytic powder prepared in Example 1 were analyzed using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDS). To further verify the macroscopic and microscopic structural integrity of the Fe2Mn-500 catalytic powder prepared in Example 1 after film formation on the support surface, the constructed Fe2Mn-500 catalytic film was characterized by cross-sectional and top-view SEM-EDS.

[0134] 2. Test Results and Analysis: Morphological Inheritance: By Figure 1 SEM images show that the prepared catalyst fully inherits the rod-like morphology of the Mn-MOF-74 precursor. This hierarchical rod-like structure is interwoven, which is beneficial for forming a highly permeable porous network after film formation.

[0135] Nanoscale confinement verification: by Figure 3 HRTEM images revealed that extremely small, non-aggregated metal nanoparticles were uniformly distributed within the porous carbon matrix. The particles were firmly encapsulated by the carbon layer, demonstrating the effectiveness of the "subject-object" confinement strategy described in this invention.

[0136] Component distribution: Figure 2 and Figure 4 EDS mapping showed that the five elements Fe, Mn, C, N, and O were highly overlapped and uniformly distributed within the single rod-shaped structure. This demonstrates that, through the preparation method of this invention, the iron component has been successfully infiltrated and uniformly confined within the manganese-based framework, constructing bimetallic active centers. Figure 5 The cross-sectional SEM images clearly show that the catalyst active layer is uniformly and smoothly deposited on the surface of the supporting substrate, forming a structure with obvious interfaces. The average thickness of the active catalyst layer was measured to be approximately 91.5 μm. Figure 6 Cross-sectional EDS mapping images of af show that the five elements C, O, Mn, Fe, and N all exhibit continuous, uniform, and high-intensity signal distributions within the 91.5 μm thick active catalytic layer. Figure 7 Image ac is a top-view SEM image of the catalyst film surface. Observation at different magnifications shows that the catalyst film surface is extremely smooth, dense, and free of cracks or defects.

[0137] Test Example 2: Phase Structure Analysis

[0138] This test case aims to demonstrate the regulatory effect of the pyrolysis process on the catalyst phase.

[0139] 1. Testing methods: X-ray diffraction (XRD) was used to analyze the phase composition of the material, and X-ray photoelectron spectroscopy (XPS) was used to analyze the valence states of surface elements.

[0140] 2. Test Results and Analysis: Phase Transformation: From Figure 8 The XRD patterns show that after pyrolysis at 500℃, the organic ligand peaks of the precursor completely disappeared, transforming into broad carbon peaks and characteristic diffraction peaks of Fe / Mn oxides. This indicates that the organic framework has been successfully transformed into a catalytically active carbon-based bimetallic composite material.

[0141] Evidence of valence state cycles: XPS spectra ( Figure 9 (a) and (b) confirmed the existence of the Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II) multivalent redox couples.

[0142] Test Example 3: Reactive Oxygen Species (ROS) Identification and Catalytic Mechanism Analysis

[0143] This test case aims to reveal the intrinsic mechanism of pollutant degradation by the triple synergistic system of "membrane filtration-nano confinement-micro-nano bubbles" at the molecular level, and to identify key active substances in the reaction process.

[0144] 1. Test Method: Free Radical Quenching Experiment: Different concentrations of tert-butanol (TBA, for quenching ·OH), furfuryl alcohol (FFA, for quenching 1O2), and p-benzoquinone (p-BQ, for quenching O2) were added to the reaction system of Example 1. ·- The dominant bioactive species can be determined by observing changes in the degradation rate.

[0145] 2. Test Results and Analysis: Free Radical Recognition: Quenching experiment results show that... Figure 14 As shown in Figure a, the degradation of oxalic acid was most significantly inhibited after the addition of TBA, indicating that ·OH is the main oxidizing agent in the system. Meanwhile, Figure 14 b and 14c show that FFA and p-BQ also caused varying degrees of rate decrease, confirming the non-radical pathway ( 1 O2) and superoxide radicals (O2) ·- (and) joint participation.

[0146] Mechanism Summary: Test data show that the Fe(III) / Fe(II) and Mn(IV) / Mn(III) / Mn(II) redox pairs within the nanoconfined channels exhibit a strong synergistic effect. When micro / nanobubbles (MNBs) are intercepted and compressed by the membrane channels, this high-pressure microenvironment accelerates electron transfer and induces the generation of high-flux active species.

[0147] Test Example 4: Long-term operational stability of nano-confined catalytic membranes

[0148] This test case aims to verify the structural stability and environmental safety of the nanoconfined structure provided by the present invention under continuous industrial operation scenarios.

[0149] 1. Test Method: Long-term filtration experiment: The Fe2Mn-500 catalytic membrane prepared in Example 1 was continuously operated for 720 min in an ozone micro-nano bubble synergistic system. The oxalic acid removal rate was recorded every 60 min.

[0150] 2. Test Results and Analysis: Activity Stability: During continuous operation for 720 min ( Figure 12 The removal rate of oxalic acid has consistently remained above 94%. Figure 13 No significant performance degradation was observed, demonstrating that the catalytic active sites have extremely high stability under oxidizing conditions.

[0151] 3. Conclusion: This test case fully demonstrates that the catalytic membrane described in this invention not only has excellent degradation performance but also a long lifespan, meeting the application requirements of practical water treatment projects.

[0152] In summary, the nano-confined catalytic membrane (Fe2Mn-500) provided by this invention exhibits significantly better activation effects in the flow-through filtration mode compared to the traditional non-flow-through stirring mode when synergistically removing organic pollutants with ozone micro-nanobubbles (O3-MNBs). Under flow-through operation, the forced convection effect generated by membrane filtration effectively reduces the diffusion layer thickness on the surface of the active catalytic layer, significantly enhancing the mass transfer coefficient of the micro-interface. This, in turn, promotes more efficient contact between ozone micro-nanobubbles and the active sites confined within the carbon nanopores.

[0153] The triple synergistic mechanism of "membrane filtration-nano confined catalysis-micro / nano bubbles" not only significantly accelerates the reaction rate and improves the degradation and mineralization efficiency of pollutants such as oxalic acid, antibiotics, and dyes, but also fully utilizes the active sites of the catalyst through interfacial enhancement, fundamentally solving the problems of low ozone utilization and limited mass transfer, and significantly improving the overall catalytic performance of the system. Compared with the non-flow-through mode, the flow-through operation mode effectively reduces the system's operating energy consumption and ozone addition costs while ensuring high-efficiency degradation, providing a scientific and reliable technical solution for the continuous, controllable, and industrial-scale optimized treatment of recalcitrant organic wastewater.

[0154] The embodiments shown in this specification are only used to illustrate the technical solutions of the present invention and are intended to help those skilled in the art understand the principles and advantages of the present invention. They do not constitute a limitation on the scope of protection of the present invention. Although the present invention has been specifically described, those skilled in the art can still make any modifications, equivalent substitutions or other reasonable variations to the implementation methods without departing from the spirit and scope of the present invention. All equivalent technical solutions resulting therefrom should be considered within the scope of protection of this patent.

Claims

1. A method for preparing a nano-confined catalytic membrane, characterized in that, Includes the following steps: S1. Dissolve the manganese source and surfactant in a mixed solvent to form solution A; The ligand was dissolved in a mixed solvent to form solution B; solution B was slowly added to solution A, and the mixture was stirred at 25°C for 18-20 h. After that, the mixture was centrifuged, washed, and dried to obtain the Mn-MOF-74 precursor with a rod-like structure. S2. Using a subject-object confinement strategy, the Mn-MOF-74 precursor is dispersed in an iron source solution for impregnation treatment, so that iron ions diffuse into the nanopores of Mn-MOF-74, and iron-loaded MOF composite is obtained after post-treatment. S3. The iron-supported MOF composite is pyrolyzed under an inert atmosphere to obtain a nano-confined catalyst. S4. The catalyst and binder are mixed and dispersed in a dispersion, loaded onto the surface of a support membrane using a vacuum-assisted self-assembly method, and dried to obtain the nano-confined catalytic membrane.

2. The method for preparing the nano-confined catalytic membrane according to claim 1, characterized in that, In step S1, the manganese source is manganese acetate tetrahydrate, the ligand is trimesic acid, and the surfactant is polyvinylpyrrolidone; the mass ratio of the manganese source to the surfactant is 1:1, and the molar ratio of the manganese source to the trimesic acid is 3:2; the mixed solvent is a mixture of ethanol and water with a volume ratio of 1:

1.

3. The method for preparing the nano-confined catalytic membrane according to claim 1, characterized in that, In step S2, the iron source is ferric nitrate nonahydrate; the mass-to-volume ratio of the Mn-MOF-74 precursor to the ferric nitrate nonahydrate ethanol / water mixed solution is 1 g : 125 mL, the concentration of the iron source in the ferric nitrate nonahydrate ethanol / water mixed solution is 2 mM, and the immersion time is 30 min.

4. The method for preparing the nano-confined catalytic membrane according to claim 1, characterized in that, In step S3, the pyrolysis temperature is 400-600℃, the inert atmosphere is nitrogen, and the heating rate is 5℃·min. -1 The heat preservation time is 2 hours.

5. The method for preparing the nano-confined catalytic membrane according to claim 4, characterized in that, In step S3, the pyrolysis temperature is 500 °C.

6. The method for preparing the nano-confined catalytic membrane according to claim 1, characterized in that, In step S4, the binder is polyvinylidene fluoride, the dispersion is anhydrous ethanol, the mass ratio of the catalyst to the binder is 1:0.12, the drying temperature is 60 ℃, and the drying time is 12 h.

7. The method for preparing the nano-confined catalytic membrane according to claim 1, characterized in that, In step S4, the supporting membrane is an organic filter membrane; the thickness of the active catalytic layer of the obtained catalytic membrane is 91.5 μm.

8. A nano-confined catalytic membrane prepared by the preparation method according to any one of claims 1-7, characterized in that, Fe / Mn active sites are confined within the carbon framework in the form of ultrafine nanoparticles.

9. A method for removing organic pollutants using the nano-confined catalytic membrane as described in claim 8 in conjunction with ozone micro-nano bubbles, characterized in that, Includes the following steps: Ozone micro-nano bubbles (O3-MNBs) are generated by an ozone micro-nano bubble generator and introduced into a reaction system containing the target pollutant to enhance mass transfer. A pump is used to drive a reaction system containing O3-MNBs through the nano-confined catalytic membrane. In the micro-region at the catalytic membrane interface, the pollutants, ozone micro-nano bubbles and confined active sites are fully contacted by forced convection mode to carry out catalytic oxidation reaction.

10. The method for removing organic pollutants according to claim 9, characterized in that, The organic pollutant is at least one of oxalic acid, tetracycline, oxytetracycline, chlortetracycline, rhodamine B, methylene blue, and methyl orange.